2022
DOI: 10.1093/nar/gkac631
|View full text |Cite
|
Sign up to set email alerts
|

mRNA- and factor-driven dynamic variability controls eIF4F-cap recognition for translation initiation

Abstract: mRNA 5′ cap recognition by eIF4F is a key element of eukaryotic translational control. Kinetic differences in eIF4F–mRNA interactions have long been proposed to mediate translation-efficiency differences between mRNAs, and recent transcriptome-wide studies have revealed significant heterogeneity in eIF4F engagement with differentially-translated mRNAs. However, detailed kinetic information exists only for eIF4F interactions with short model RNAs. We developed and applied single-molecule fluorescence approaches… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 101 publications
2
15
0
Order By: Relevance
“…Conversely, another smFRET study found that partial human eIF4G (557-1137) alone slightly affects eIF4E binding kinetics, but the human eIF4F complex substantially changes the eIF4E-cap association 46 . Interestingly, free eIF4A enhances eIF4E cap accessibility via direct eIF4A-RNA contact, which is similar to the role of eIF4G in eIF4E 25 . Meanwhile, the binding of eIF4F to RNA results in the dissociation of eIF4E from eIF4F shortly after the formation of the eIF4F-RNA complex, but this process is dependent on ATP hydrolysis (0.07-0.08 s -1 ; Fig.…”
Section: Smfi Studies In Mrna Circularizationmentioning
confidence: 56%
See 4 more Smart Citations
“…Conversely, another smFRET study found that partial human eIF4G (557-1137) alone slightly affects eIF4E binding kinetics, but the human eIF4F complex substantially changes the eIF4E-cap association 46 . Interestingly, free eIF4A enhances eIF4E cap accessibility via direct eIF4A-RNA contact, which is similar to the role of eIF4G in eIF4E 25 . Meanwhile, the binding of eIF4F to RNA results in the dissociation of eIF4E from eIF4F shortly after the formation of the eIF4F-RNA complex, but this process is dependent on ATP hydrolysis (0.07-0.08 s -1 ; Fig.…”
Section: Smfi Studies In Mrna Circularizationmentioning
confidence: 56%
“…Recognition of eIF4G increases eIF4E's affinity to a cap or cap analog 44,45 . To study the 5' cap-binding kinetics of eIF4E, smFRET was monitored with fluorescently labeled eIF4E in the absence and presence of eIF4G 25,46,47 (Fig. 2a).…”
Section: Smfi Studies In Mrna Circularizationmentioning
confidence: 99%
See 3 more Smart Citations